IMPLEMENTASI PENDEKATAN KONSTRUKTIVISME BERBASIS PEMBELAJARAN BERDIFERENSIASI TERKAIT MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS 2 DI SDN 023 KUARO - Suminah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is based on the low learning motivation of students, as indicated by the lack of active participation in learning, particularly in Mathematics. This study aims to describe the implementation of a constructivist approach in improving students’ learning motivation through differentiated instruction in Mathematics for second-grade students at SDN 023 Kuaro. This research uses a qualitative approach with respondents consisting of teachers, students, and the school principal. Respondents were selected using purposive sampling based on the research objectives. Snowball sampling occurred through the involvement of participants relevant to the main respondents. The research procedure began with the preparation of instruments and instructional tools based on the constructivist approach. The research was carried out through interviews and observations. Data analysis involved drawing preliminary and final conclusions during the interview process. The results of the study, obtained from teacher respondents, indicate that they have prepared, implemented, and evaluated student engagement and understanding using cooperative and collaborative strategies. Student respondents have prepared, carried out, and completed group tasks, while the principal has facilitated the preparation, implementation, and evaluation processes.